1982
DOI: 10.1161/01.hyp.4.6.817
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular response in black and white hypertensives.

Abstract: SUMMARY Sixteen untreated black patients with mild-to-moderate hypertension and no evidence of target organ damage were matched for age, sex, casual blood pressure (BP), and socioeconomic status with 16 white hypertensives. All patients were studied under standardized conditions in the hospital where they underwent continuous intraarterial ambulatory monitoring of BP and assessment of BP control mechanisms. BP characteristics over prolonged periods of recording were similar for both groups, as were sinoaortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
(13 reference statements)
1
17
0
Order By: Relevance
“…30 Interestingly, when recent (ie, less than a decade ago) migrants from West Africa to the United States were compared with native (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 17t (13)(14)(15)(16)(17)(18)(19)(20) 17t (14)(15)(16)(17)(18)(19)(20) African Americans and US whites, both US whites and the recent African migrants had a persistent nocturnal decline in systolic blood pressure, which was not seen in native African Americans. 31 Studies of Barbadian blacks have also shown that the usual decline in nocturnal blood pressure is preserved.…”
Section: Resultsmentioning
confidence: 99%
“…30 Interestingly, when recent (ie, less than a decade ago) migrants from West Africa to the United States were compared with native (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 17t (13)(14)(15)(16)(17)(18)(19)(20) 17t (14)(15)(16)(17)(18)(19)(20) African Americans and US whites, both US whites and the recent African migrants had a persistent nocturnal decline in systolic blood pressure, which was not seen in native African Americans. 31 Studies of Barbadian blacks have also shown that the usual decline in nocturnal blood pressure is preserved.…”
Section: Resultsmentioning
confidence: 99%
“…However, several other studies of renal function and electrolytes excretion of freeliving black and white children revealed no differences between the blacks and whites in sodium excretion. 9,13,17,36 Similarly, lower PRA in blacks compared with whites has also been reported even when there were no significant differences in urinary sodium. Moreover, low PRA has also been found in blacks on diets where the intake of sodium has been carefully controlled and lower PRA has been found on both low and high sodium intakes.…”
Section: Dietary Sodium and Potassium Intakementioning
confidence: 88%
“…12,28 Renin release and the sympathetic system Adrenergic receptors are found on JGA cells and there is considerable evidence demonstrating that even moderate increases in renal sympathetic activity leads to increases in renin release through ␤-adrenergic receptor stimulation; by contrast, there is still controversy on the role of ␣-adrenergic activation as both inhibition and activation of renin release have been reported. 26 No major and consistent differences in circulating catecholamines between blacks and whites under basal conditions have been reported, [35][36][37] though this does not exclude differences in sympathetic activity as plasma levels of catechoamines are not a good index of adrenergic activity. Reduced plasma levels of dopamine ␤-hydroxylase (DBH) have been described in both black adults and in children compared with whites.…”
Section: Renin-angiotensinogen Reactionmentioning
confidence: 99%
“…Differences in results obtained using ABPM devices made by different manufacturers have been reported. 14 Two reports included here report data obtained through intraarterial monitoring during inpatient hospitalization, 22,31 which may result in fewer artifactually induced increases in nocturnal blood pressure due to cuff inflation.…”
Section: Discussionmentioning
confidence: 99%